Family secrets: stories of incest and sexual violence in Mexico - González-López, Gloria (Latina / o sociology series, 2015)
Acknowledgments / Con profunda gratitud -- En familia : sex, incest, and violence in Mexican families -- Conjugal daughters and marital servants : the sexual functions of daughters in incestuous families -- A la prima se le arrima : sisters and primas -- Nieces and their uncles -- Men's life stories -- Toward a feminist sociology of incest in Mexico -- Appendix A. Study participants -- Appendix B. Methodological considerations -- Appendix C. Incest in 32 Mexican state penal codes -- Appendix D. Uncle-niece cases -- Notes -- References -- Index -- About the author